A Local Dental Network Approach to the COVID-19 Pandemic: Innovation Through Collaboration. Issue 1 (March 2021) - Hearnshaw, Simon; Serban, Stefan; Mohammed, Imran; Zubair, Ajmal; Jaswal, Deksha; Grant, Siobhán
The coronavirus pandemic has had significant effects on individuals, healthcare systems and governments. In the UK, whilst routine dentistry was suspended, an urgent dental care system was required to support urgent patient need. Using an adapted model of Donabedians' framework, a critical evaluation of the services developed and implemented is provided and the various innovative approaches involved in this work are discussed. The three domains of the framework are structure, process and outcome. Structure: We present the principles for selecting and initiating hubs, the integration with secondary care services and the supply of personal protective equipment. Process: The main elements are communication, the development of referral processes to manage complex cases and data collection. Outcome: Through work with local dental stakeholders, 23 clusters and 36 hubs were set up covering a large geographical area. The integrated network of hubs and clusters has strengthened collaboration between providers and policy makers. Various leadership approaches facilitated the readiness for the transition to recovery. The new local collaborative structures could be used to support local programmes such as flexible commissioning, peer-led learning and integration with primary care networks.